Analyzing Gojek service quality and customer satisfaction using Servqual–Canoe Model–QFD integration - Trenggonowati, Dyah Lintang; Ulfah, Maria; Sukamto, Aurora Elvaretta (Universitas Sultan Ageng Tirtayasa, 2023)
The problem at the Untirta Faculty of Engineering concerning Go-ride services is a decrease in Go-ride users from 2020 to 2022. This decline is due to users' complaints about unsatisfactory Go-ride services, such as drivers being unfriendly and impolite, among other issues. Based on the challenges faced by Gojek, a study was conducted on service quality using the Servqual, Canoe, and Quality Function Development (QFD) methods. This study aims to identify attributes that fail to meet customer expectations, determine priority attributes for improvement, and prioritize improvement efforts that the company can undertake to enhance the quality of Go-ride services. Questionnaires were distributed to 97 respondents. The research findings revealed 8 attributes with a negative gap. The priority attribute requiring improvement is drivers consistently being friendly and polite to customers, with an adjusted importance value of 5.46. Furthermore, the suggested improvement that the company can pursue is to reward drivers who consistently adhere to the standard operating procedures (SOP), with a relative weight percent value of 51.03%. In conclusion, there are 8 customer needs that still do not meet expectations, with the priority being drivers' consistent friendliness and politeness. The suggested priority improvement for the company involves rewarding drivers who consistently adhere to SOP.